"I'm just different–that's all–I'm so sorry … ": Black men, ASD and the urgent need for DisCrit Theory in police encounters. Issue 3 (5th April 2022) - Hutson, Turea Michelle; McGhee Hassrick, Elizabeth; Fernandes, Sherira; Walton, Jessica; Bouvier-Weinberg, Kathryn; Radcliffe, Antoinette; Allen-Handy, Ayana
Abstract : Purpose: Limited research focuses on the challenges that exist at the intersection of race and dis/ability for Black men on the autism spectrum in encounters with law enforcement. An interdisciplinary approach is necessary to fully comprehend and mitigate the complex challenges. This conceptual article presents Critical Dis/ability (DisCrit) Theory, a framework usually applied to education, as a lens through which to think about encounters between Black autistic men and police officers. The article concludes with recommendations for collaboration between social scientists, police scholars, law enforcement and the public to improve the outcomes of police encounters involving Black men on the autism spectrum. Design/methodology/approach: Using a literature review and analysis of current events, this conceptual article explores the intersections of race and disability, specifically neurodiversity, in policing using Critical Dis/ability (DisCrit) theory, and its predecessors, Intersectionality Theory and Critical Race Theory (CRT). Findings: An interdisciplinary approach might be a potential solution to improve police encounters with Black autistic men. Expanding the theoretical frameworks utilized in scholarship about policing might allow for innovative approaches to examine current practices in law enforcement. Collaboration and critical dialogue may yield opportunities for further research and shifts in practice. Originality/value: This conceptual article uses two incidents from recent events to highlight the need for increased scholarship around the intersections of autism and race, with a particular focus on Black autistic men. It advocates for the use of social science frameworks, namely DisCrit Theory, as a novel way to approach new research regarding race and dis/ability.